Generalized Molluscum Contagiosum Successfully Treated with Interferon-Alpha in a Patient with Folliculotropic Mycosis Fungoides - Melchers, Rutger C. (Case Rep Dermatol, 2019)
We present the case of a 50-year-old patient with folliculotropic mycosis fungoides (FMF) unresponsive to retinoids and the chemotherapeutic regimens CHOP, gemcitabine, and brentuximab-vedotin. During immunosuppressive therapy, the patient developed extensive progressive molluscum contagiosum. The mollusca did not respond to topical imiquimod but showed a swift complete response to interferon-alpha 2a (IFNa). Recently, the patient started with alemtuzumab as induction therapy for an allogenic stem cell transplantation and simultaneously continued IFNa therapy.